Temperature-Programmed Desorption of H2 from Mg-Ni/C for Hydrogen Storage Application - Rudypratama, Billy; Nurfitrah, Aditya Eka; Ismoyojati, Rizki; Priyono, Bambang (Indonesian Journal of Chemistry, 2025)
Hydrogen is a flexible energy carrier with the potential to replace fossil fuels as a clean and renewable energy source. However, efficient storage systems under ambient conditions are essential for practical applications. This study investigates magnesium–nickel-based metal hydrides for hydrogen storage, enhanced with 20% graphite or additional nickel. The synthesized samples—MgNi2, MgNi2 + graphite 20%, Mg2Ni + graphite 20%, and Mg2Ni + Ni 1:1—were characterized using XRD, BET, SEM-EDX, and hydrogen temperature-programmed desorption (TPD). Crystallite sizes were found to be 132.125, 137.125, 77.168, and 92.335 nm, respectively. BET analysis revealed surface areas of 2.144, 1.664, 7.113, and 2.308 m2/g, corresponding pore volumes of 0.0038, 0.0031, 0.0137, and 0.0100 cm3/g. TPD results showed that Mg2Ni + graphite 20% had the fastest desorption rate (46 min), consistent with its highest surface area and pore volume. This sample also achieved the highest hydrogen adsorption capacity at 0.0615 mmol/g. These findings demonstrate that Mg-Ni hydrides, especially those modified with graphite, offer promising performance for hydrogen storage applications, particularly in systems requiring rapid desorption and efficient kinetics, such as fuel-cell electric vehicles. The results highlight the potential of tailored Mg-Ni composites for advanced hydrogen storage solutions.